A study on level of awareness of tax payers in Southern Region towards Goods and Services Tax (GST) / Asri Osman and Nabilah Khirrudin - Osman, Asri; Khirrudin, Nabilah (Faculty of Business and Management, 2014)
Tax has been recognized as one of the main sources of government income. Goods and Services Tax (GST) or also known as Value Added Tax (VAT) in many countries is a multi-stage consumption tax on goods and services. Starting year 2015, Malaysia will implement GST like many countries such as Canada, Australia and New Zealand. Goods and Services Tax is a tax imposed on the sale of goods and services. In recent years, this issue on GST has been raised by the Malaysian Government as an approach to reduce its deficit. This study is attempt to investigate Malaysian awareness towards upcoming of the GST implementation.